Computational prediction of performance for a full scale Isamill: Part 1 – Media motion and energy utilisation in a dry mill. (August 2015) - Cleary, Paul W.; Sinnott, Matt D.; Pereira, Gerald G.
Highlights: DEM has been used to study the behaviour of a full industrial scale Isamill. They key factor controlling charge behaviour is the force balance near the discs. Gravity provides a critical restoring force that presses the media against the discs. The disc holes play a key role in media transport generating high speeds jets. The effects of changes in mill parameters and media on performance are identified. Abstract: The Isamill is a horizontal stirred media mill used for fine and ultrafine grinding. Discrete Element Method (DEM) simulation has been used in this paper to study the behaviour of the media and the collisional environment in a full industrial scale Isamill. The DEM modelling has been able to provide a general understanding of the force balances that control the mill performance and the quantitative variation of key performance measures such as power draw and peak collision energy with changes in mill operating parameters and media properties. The key factor controlling the behaviour of the media and mill performance is the force balance on the media adjacent to the rotating discs of the impellor. Gravity and any applied axial pressure gradient play a critical role by providing a restoring force that presses the media bed against the discs which enables energy transfer from the discs to the adjacent media. Three important aspects of the media flow are identified with the holes in the discs playing a critical role in media transport and generating high speeds media jets in the upper half of the mill.